PEMETAAN KOLABORATIF SITUASIONAL PADA KONDISI DARURAT - Yusri Habibah Wahyuni; Budi Hartono (Jurnal Teknosains, 2015)
The first step to do disaster management accurately is getting comprehensive information about disaster. A situational map is the overview of the disaster situation based on geo-spatial information at a particular time. This map is a tool which can gain comprehensive information in emergency. This study aims to complement earlier research with re test confidence level variable that is divided for object detection, type, and location. Besides this study examines collecting information system in emergency situation model that used to be used by police agencies which is using mediator. this study is conducted by experiments that involved 48 participants that were divided in 16 groups. The participants sample consisted of wide variety of different majority and educational level in UGM and non UGM with age range between 19 and 29 years old (Mean = 24; SD = 2.68). The whole experiments are collaboration, collaboration with confidence level and collaboration with mediator. Assessments of experiment accuracy were used three kinds which are checklist, detection and position of objects. Another factor that is considered is prior knowledge of mediator and respondent. This study using α = 5% and ANOVA showed position information more accurate with confidence level model. Other information like checklist and detection could using all model. Prior knowledge have not affected in improving map accuracy.